The nature and significance of the Faroe-Shetland Terrane: Linking Archaean basement blocks across the North Atlantic - Holdsworth, R.E.; Morton, A.; Frei, D.; Gerdes, A.; Strachan, R.A.; Dempsey, E.; Warren, C.; Whitham, A. (Precambrian Research, 2018)
Core samples of the continental basement rocks that underlie the eastern Faroe-Shetland Basin (FSB) and its inshore margins west of Shetland reveal a suite of predominantly granodioritic to granitic orthogneisses (including TTG), together with lesser volumes of foliated granitoids and subordinate dioritic to mafic gneisses and amphibolites. A small area of lithologically similar gneisses also crops out onshore at North Roe/Uyea west of the Caledonian front in Shetland. Coarse grained gneissose textures and mineralogies consistent with upper amphibolite facies metamorphism are overprinted by a weak, but ubiquitous static greenschist facies retrogression. Later structures include widespread epidote-quartz veining, and local developments of mylonite, cataclasite, pseudotachylite and phyllonite. Regions associated with the Rona Ridge oil fields (e.g. Clair, Lancaster) also preserve extensive brittle fracturing and associated low temperature hydrothermal mineralization (quartz, adularia, calcite, pyrite/chalcopyrite) with significant fracture-hosted hydrocarbons. New and published U-Pb zircon analyses from the gneisses offshore give a relatively narrow range of Neoarchean protolith ages (ca 2.7-2.8 Ga) spread over a geographic area of 60,000km2 west of Shetland. Detrital zircon data from overlying Triassic-Cretaceous sedimentary sequences in the FSB suggest an equivalent limited range of Neoarchean source materials. Our findings suggest that a major phase of Neoarchean crustal formation and associated high grade metamorphism dominates basement rocks in the region. They are similar in age and lithology to the protoliths of the nearest onshore Lewisian Complex of NW Scotland (Rhiconich Terrane). However, they lack geochronological or textural evidence for the widespread Proterozoic Laxfordian events (ca 1.7-1.8 Ga) which are widespread in Scotland. This suggests that the Precambrian rocks west of Shetland – the Faroe-Shetland Terrane-can be correlated with the Archean rocks of the Central Greenland-Rae Craton and that ...